2013
DOI: 10.2141/jpsa.0130006
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Organ Weights and, Blood Parameters of Broilers Fed Diets Containing Graded Levels of Dietary Canola Meal and Supplemental Copper

Abstract: An experiment with 495 one-day-old male broiler chicks was conducted to investigate the effects of different dietary levels of canola meal (0, 10, 20%) and copper (0, 125, 250 mg/kg) on performance, carcass characteristics and some blood parameters. A completely randomized design with 3×3 factorial arrangement was used with 5 replicates from 1 to 42 of age. Feed intake was not significantly affected by treatments during 1 to 21 d, 21 to 42 d and throughout the study (P>0.05). The body weight gain and feed conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
9
8
1
Order By: Relevance
“…This could be attributed to the lower CM glucosinolates and sinapine of our dietary CM that was not adequate to affect the FI. The current findings are in line with previous reports on CM usage in broiler chickens without any effect on FI (Payvastegan et al, 2013;Gopinger et al, 2014;Aljuobori et al, 2016;Zhang and Adeola, 2016 An increase in dietary level of CM reduced BWG of the chickens. This could be due to presence of antinutritional factors mainly fiber (12.9%) and glucosinolates (23.5 μmol/g) in the CM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This could be attributed to the lower CM glucosinolates and sinapine of our dietary CM that was not adequate to affect the FI. The current findings are in line with previous reports on CM usage in broiler chickens without any effect on FI (Payvastegan et al, 2013;Gopinger et al, 2014;Aljuobori et al, 2016;Zhang and Adeola, 2016 An increase in dietary level of CM reduced BWG of the chickens. This could be due to presence of antinutritional factors mainly fiber (12.9%) and glucosinolates (23.5 μmol/g) in the CM.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our results, Newkirk and Classen (2002), Maroufyan and Kermnshahi (2006), Kermnshahi and Abasi pour (2006), Woyengo et al (2011) and Payvastegan et al (2013) reported the increased liver size of broilers due to dietary inclusion of CM. Accordingly, the AST and ALT activity determined in the current study also showed the significant rise as a result of increased dietary CM level.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Many studies (Jegede, Oduguwa, Bamgbose, Fanimo, & Nollet, ; Kumar et al., ; Payvastegan, Farhoomand, & Delfani, ; Samanta, Biswas, & Ghosh, ; Zahedi, Ghalehkandi, Ebrahimnezhad, & Emami, ) have shown a reduction in cholesterol levels after adding Cu to poultry diets, which is in agreement with our results. This can be explained, in that adding higher levels of Cu will regulate cholesterol biosynthesis indirectly by decreasing the reduced form of glutathione and increasing the oxidised form of glutathione (Bakalli, Pesti, Ragland, & Konjufca, ; Kim, Chao, & Allen, ).…”
Section: Discussionsupporting
confidence: 92%
“…The relative liver weight was affected by both forms of Cu and was significantly lower at higher concentrations of Cu in relation to the control group. The liver results are consistent with the results of (Shahzad et al., ; Skrivan, Skrivanova, Marounek, Tumova, & Wolf, ), while in other studies (Mroczek‐Sosnowska, Łukasiewicz et al., ; Payvastegan et al., ; Upadhaya, Lee, & Kim, ; Wang et al., ), the liver weight was not affected. It was reported that a high concentration of Cu‐NP negatively affected the histology of the liver, kidneys and spleen, but not the heart and lungs in rats, and these changes were well supported by organ weight changes (Lee et al., ).…”
Section: Discussionsupporting
confidence: 91%